Crisis management in art: Selangor Galleries’ COVID-19 pandemic responses / Khairul Ehsani Sapari and Mohd Fuad Md Arif - Sapari, Khairul Ehsani; Md Arif, Mohd Fuad (Faculty of Art and Design, 2025)
The COVID-19 pandemic profoundly impacted the art industry, disrupting traditional operations and requiring rapid adaptation. This study examines the early crisis responses of three major art galleries in Selangor—one public and two private—filling a gap in the literature on local galleries' resilience strategies during the pandemic. Utilising a qualitative case study approach, the research collected data through interviews conducted simultaneously with all three gallery managers. Findings reveal that the galleries implemented a range of adaptive strategies, including digital engagement initiatives, restructured exhibitions, and enhanced community outreach programs. These measures not only mitigated the immediate impacts of the pandemic but also fostered long-term resilience and innovation within the galleries. Beyond individual gallery narratives, this study offers unique insights into how local art institutions adapt during crises, contributing valuable knowledge to art management and providing practical implications for future crisis preparedness in the sector.